(untitled) (Sociologisk Forskning, 1995)
The social-psychological conditions and obstacles to environmentally responsible agency - a theoretical perspective The aim in this article has been to go beyond the individual level in theoretically analyzing the preconditions for people to adopt a more environmentally responsible behavior within daily activities. In the first part, I have examined some overlapping social characteristics of modernity. The chief concepts here have been risk, time-space distanciation, disembeddedness and reflexivity. Anthony Giddens (1990) and Ulrich Beck (1986/1992) are referred to in this part. These modem characteristics have been put in relation to the motivational factors of behavior change offered in modem urban society. In the second part, the question of environmentally related agency has been placed into three social-psychological contexts: the public, the private, and the parochial realms of social life. I have argued that the different realms to various extents are affected by the modem characteristics, and that the different realms, therefore, offer different conditions for the environmentally responsible behavior to be supported by socially, ethically and, practically motivating factors. Emphasis has been given upon motivating factors within the local realm, mainly within neighborhoods. In neighborhoods, I have claimed, social ties, trust between neighbors, and a shared interest for the neighborhood may be used as an intermediate variable between the leading institutions of society and the individual lifestyle in solving environmental problems. This is true both when the environmental goals of the leading institutions, are communicated to the parochial sphere and vice versa. I have also suggested further theoretical analyses as well as possible empirical applications to the theoretical framework of the article.